Porphyromonas gingivalis Sphingolipid Synthesis Limits the Host Inflammatory Response. (May 2020) - Rocha, F.G.; Moye, Z.D.; Ottenberg, G.; Tang, P.; Campopiano, D.J.; Gibson, F.C.; Davey, M.E.
Porphyromonas gingivalis, like other bacteria belonging to the phylum Bacteroidetes, synthesizes sphingolipids (SLs). However, their exact roles in microbial physiology and their potential role in mediating interactions with their eukaryotic host are unclear. Our working hypothesis for this study was that synthesis of SLs (host-like lipids) affords a mechanism that allows P. gingivalis to persist in homeostasis with its host. In a previous study, we deleted a gene (PG1780 in strain W83) predicted to encode a serine palmitoyl transferase (SPT)—the enzyme that catalyzes the first conserved step in the synthesis of SLs—and we determined that the mutant was unable to synthesize SLs. Here, we characterized the SPT enzyme encoded by PG1780, analyzed the impact of SPT deletion on P. gingivalis gene expression (RNA-Seq analysis), and began to define the impact of SL synthesis on its interactions with host cells. Enzymatic analysis verified that the protein encoded by PG1780 is indeed an SPT. RNA-Seq analysis determined that a lack of SL synthesis results in differential expression of extracytoplasmic function sigma factors, components of the type IX secretion system (T9SS), and CRISPR and cas genes. Our data demonstrate that when human THP1 macrophage-like cells were challenged with the wild type (W83) and the SL-null mutant (W83 ΔSPT), the SL-null strain elicited a robust inflammatory response (elevated IL-1β, IL-6, IL-10, IL-8, RANTES, and TNFα) while the response to the parent strain W83 was negligible. Interestingly, we also discovered that SLs produced by P. gingivalis can be delivered to host cells independent of cell-to-cell contact. Overall, our results support our working hypothesis that synthesis of SLs by P. gingivalis is central to its ability to manipulate the host inflammatory response, and they demonstrate the integral importance of SLs in the physiology of P. gingivalis .